Computation studying of the neutron yield from the neutron-production target irradiated with electrons - Prokhorets, I.M.; Prokhorets, S.I.; Rudychev, Y.V.; Skrypnik, A.I.; Fedorchenko, D.V.; Khazhmuradov, M.A. (Вопросы атомной науки и техники, 2009)
It is considered the modeling of neutron yield from the targets with high atomic numbers irradiated with accelerated electrons. Modeling results from the MCNPX and GEANT software are compared with existing experimental results and deterministic calculations